Roll-to-roll redox-welding and embedding for silver nanowire network electrodes. Issue 39 (27th September 2018) - Kim, Yeontae; Sul, Yeong Eun; Kang, Hyungseok; Choi, Yongsuk; Lim, Ho Sun; Lee, Sungjoo; Pu, Lyongsun; Yi, Gi-Ra; Cho, Sung Min; Cho, Jeong Ho
Abstract : We developed a continuous roll-to-roll redox-welding and embedding method for the fabrication of electrodes of silver nanowire (AgNWs) networks. Abstract : We developed a continuous roll-to-roll redox-welding and embedding method for the fabrication of electrodes of silver nanowire (AgNWs) networks. The roll-to-roll welding method involved a sequence of oxidation and reduction reactions in an aqueous solution. The redox-welding significantly decreased the sheet resistance of the AgNW film owing to the strong fusion and interlocking at the nanowire junction, while the optical transmittance was maintained. The first oxidation step using HNO3 generated ionized silver (Ag + ) which got re-deposited onto the nanowire junctions via an autocatalytic reaction. The oxide layers, which formed on the nanowire surface by both air exposure and the first step of oxidation, were removed by the second reduction step using NaBH4 . The redox-welded AgNW electrodes exhibited a sheet resistance of 11.3 Ω sq −1 at the optical transmittance of 90.5% at 550 nm. Furthermore, redox-welding of the AgNWs significantly enhanced their mechanical robustness compared to that of the as-coated AgNWs. The redox-welded AgNWs embedded in a UV curable resin, using a roll-to-roll embedding process, were successfully applied as anode electrodes for large-area and flexible organic light emitting diodes (OLEDs). The device performance is superior to that of a device based on the as-coated AgNW electrode, and is also comparable to that of a device using commercial ITO as the electrode. The redox-welding and embedding processes provide a facile and reliable method for fabricating large-area transparent flexible electrodes for next-generation flexible optoelectronic devices.